2022
DOI: 10.48550/arxiv.2202.02957
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Is Abell 2261 a fossil galaxy cluster in a transitional dynamical state?

Hyowon Kim,
Jongwan Ko,
Rory Smith
et al.

Abstract: Abell 2261 (A2661) is a well-studied fossil cluster, but previous studies give contradictory results on its dynamical states, such as its X-ray central entropy and magnitude gap. To improve our understanding of its dynamical state, we conduct multi-object spectroscopic observations with Hectospec on the MMT, covering an area out to 5 virial radii from the cluster center, and get improved completeness and membership. Using this new data, we calculate multiple dynamical indicators including gaussianity, distance… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 73 publications
(103 reference statements)
1
0
0
Order By: Relevance
“…Our results support the scenario in which FGs could be a transitional stage in the life of a group/cluster and that the magnitude gap can be reduced when a bright galaxy falls into the FG potential (Aguerri et al 2018;Kim et al 2022). However, we found that the largest gaps are found in FG with a low density of Fig.…”
Section: Discussionsupporting
confidence: 85%
“…Our results support the scenario in which FGs could be a transitional stage in the life of a group/cluster and that the magnitude gap can be reduced when a bright galaxy falls into the FG potential (Aguerri et al 2018;Kim et al 2022). However, we found that the largest gaps are found in FG with a low density of Fig.…”
Section: Discussionsupporting
confidence: 85%